The changing dynamics of the Kurdish question - Yılmaz, Arzu (2018)
Abstract: The Kurds in the Middle East have become significant political and military actors in the context of the fight against IS. One of the most important consequences of this situation has been the transformation of the Kurdish Question. Frustrated with the largely fruitless efforts to achieve equal rights and equal political footing in the countries where they reside, Kurdish parties have tended to change their perceptions and strategies. There is a remarkable shift under way: from the fight for "justice, freedom and equality inside a given nation state" to the "defence of Kurdistan" as a political territory. Therefore, a fragmented approach towards the Kurdish Question as a domestic issue of national concern is not realistic anymore. Developments in the Kurdish landscape require a review of the conventional stance and a comprehensive solution in order to balance competing interests and cope with the evolving challenges in the Middle East. (Autorenreferat)